The Repressive Policies of the Communist Regime: Bulgarian Muslims and Communal Memory - Borovin, Salih (Language and Public Sphere, 2024)
This article examines the chronology of the assimilation policies and the attempt to erase the group religious identity of the Pomak population in the Rhodope Mountains. Also included are short excerpts from the accounts of a small number of people who recount family memories of the trauma of the largest assimilation campaign in Communist Bulgaria.